ANALISIS HISTORITAS HADIS DI AFRIKA UTARA (MENGULAS SEJARAH INTELEKTUAL HADIS DI TUNISIA) - Al Faisal; Rofiatul Ubaidillah (Yayasan Baitul Hikmah al-Zain, 2024)
This research explores the historical and intellectual dynamics of hadith development in North Africa, particularly in Tunisia. Against a backdrop of complex political and cultural influences since the Umayyad Dynasty, the spread of hadith in Tunisia involved not only the transmission of texts but also contextualization within local culture. This study identifies three primary aspects of hadith studies in North Africa: the writing of hadith books, the impact of Islamic expansion on hadith studies, and the contributions of Tunisian scholars to the development of hadith historiography methods. Using a qualitative approach with historiographic analysis, this research delves into the intellectual aspects that accompanied hadith development in Tunisia, including hadith transmission and codification within the framework of social, political, and cultural change. The findings reveal that hadith codification in Tunisia was strongly supported by the establishment of educational institutions during the Aghlabid and Fatimid dynasties. This study seeks to fill a gap in hadith research by focusing on the mechanisms of hadith dissemination and the contributions of Tunisian scholars to hadith studies, thereby providing a broader understanding of hadith development in the Islamic world, particularly in North Africa.